The effect of advertising, brand image, price and consumer motivation on consumer purchase interest in ms.glow skincare in the Rantauprapat Region - Putri, Anike; Safri, Hayanuddin; Hasibuan, Muhammad Irwansyah (Institute of Computer Science (IOCS), 2024)
Research on the Effect of Advertising, Brand Image, Price and Consumer Motivation on Consumer Purchase Interest in Ms.Glow Skincare in the Rantauprapat Region. The purpose of this study was to determine the effect of advertising, brand image, price and consumer motivation on consumer buying interest. This study uses a quantitative approach and associative research type. The data source used is primary data source. The results showed that advertising has a positive and significant effect on buying interest, brand image has a positive and significant effect on buying interest, price has a positive and significant effect on buying interest and consumer motivation has a positive and significant effect on buying interest and advertising, brand image, price and consumer motivation together have a positive and significant effect on buying interest.